Comparison of Angiotensin-Converting Enzyme Inhibition with Angiotensin II Receptor Antagonism in the Human Forearm - John R. Cockcroft; David Sciberras; Michael R. Goldberg; James M. Ritter (1993)
Summary The object of this study was to differentiate losartan, an AT1-selective angiotensin II (ANG II) receptor antagonist, from enalapril, an angiotensin-converting enzyme (ACE) inhibitor, by measuring forearm vascular responses to AI, AII, and bradykinin. Eight healthy men were studied in a randomised, 4-period crossover study in which placebo, enalapril (10 mg), losartan (20 mg) and losartan (100 mg) were given double-blind on separate occasions. Forearm blood flow was measured by venous occlusion plethysmography during sequential infusions of ANG I, ANG II, and bradykinin into the brachial artery 4–6 h after dosing. Analysis of variance for repeated measures indicated that losartan inhibited constriction to ANG I and ANG II (both p < 0.02) in a dose-dependent manner without significantly influencing vasodilator responses to bradykinin. Enalapril (10 mg) inhibited AI similarly to losartan 100 mg without significantly influencing responses to angiotensin II, and augmented vasodilator responses to bradykinin (p < 0.0001). In human forearm vasculature, oral losartan (20–100 mg) inhibits vasoconstriction to ANG I and ANG II without significantly influencing bradykinin-induced vasodilation, whereas enalapril selectively inhibits ANG I-induced vasoconstriction while potentiating the vasodilator effect of bradykinin.